(3NeQI GdMGf TQM QSGdI CQSdGfs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g`s ((3eMeO Hf QTjO GdMaGQs)
(3ChdgG (B:s
(3GdMeO ddg GdPj WgQ bdhH ChdjGFg CeG HYO ajbhdYHO GdZfj Hf ESeGYjd Hf GdfGHdSj GdbGgQj GdfbTHfOjgPG TQM CeWQJg SeGhGJ GdgGejhVYJg ddQSGdI SjOj GQSdGf GdefShH Edi OeTb GdTGehSejJg NeQI GdMGfs
(3BNQgG (B:s
(3hSbG bHQ CMjGg MjG (B*** (3ef YXje GddWa gJGf , OGFe GdReGf eG GfYWaJ (B*** (3HGdUHG aj GdQhV CZUGfs
(3efbhdI ef fSNI GdeDda GdeDQNI SfI (B1089(3g`, hgj ebGHdI Ydi fSNI eedhcI ddTjN eMeO RjOGf GdeYQha HGdYcQ SfI (B1242(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs